A ternary memristor full adder based on literal operation and module operation. (26th April 2022) - Lin, Mi; Han, Qi; Luo, Wenyao; Wang, Xuliang; Chen, Junjie; Lyu, Weifeng
Abstract: A ternary memristor full adder is designed based on the literal operation and module‐3 plus operation. Literal operation and module‐3 plus operation are the important operations in the tri‐valued algebra system. Multiple‐valued logic can increase the amount of information carried by the signals and reduce the number of devices and connections. The combination of multiple‐valued logic and memristor is an exploration of new devices and new structures. The novel ternary memristor full adder owns the advantage of simpler structure without decoding units to convert ternary signals to binary at the terminals, and all the signals operated by the circuit are ternary. Compared with the traditional ternary full adder, the number of devices and the power consumption are greatly reduced. Simulation results of different memristor models verified the correctness and applicability of the circuit design. It provides a new idea for the design method of memristor circuits, especially multiple‐valued memristors. Abstract : This paper proposes a novel ternary memristor full adder based on the literal operation and module‐3 plus operation. The ternary memristor full adder owns the advantages of simpler structure without decoding units to convert ternary signals to binary at the terminals and lower power consumption. The applicability of the design is verified with the Biolek model, HP model, and Knowm model. It is an exploration of new devices and new structures.